Income protection for self‐employed and non‐standard workers during the COVID‐19 pandemic - Spasova, Slavina; Regazzoni, Pietro (International social security review (English edition), 2022)
Based on original evidence from the European Social Policy Network (ESPN), the article investigates the extent to which self‐employed and non‐standard workers, who are less protected by “ordinary” social protection, were included in “extraordinary” income protection and job retention schemes during the COVID‐19 pandemic in the European Union (EU) and the United Kingdom. When the crisis hit, countries quickly introduced unprecedented emergency income replacement measures for the self‐employed. Nevertheless, most of these schemes provided only basic support through lump sums and were, in some cases, subject to a variety of eligibility conditions. Non‐standard workers were in general included in job retention schemes, but substantial gaps remained in some countries. The article discusses how such gaps were addressed in five EU Member States. The article concludes by highlighting some policy pointers for better and more adequate “extraordinary” income protection for the self‐employed and non‐standard workers in times of crisis. Sur la base de données inédites du Réseau européen de politique sociale (ESPN), l’article examine dans quelle mesure les travailleurs indépendants et atypiques, qui sont moins protégés par la protection sociale «ordinaire», ont été inclus dans des régimes «extraordinaires» de protection du revenu et de maintien dans l’emploi pendant la pandémie de COVID‐19 dans l’Union européenne (UE) et au Royaume‐Uni. Lorsque la crise est survenue, les pays ont rapidement mis en place des mesures d’urgence sans précédent de remplacement du revenu pour les travailleurs indépendants. Cependant, la plupart de ces régimes ne fournissaient qu’une aide de base sous forme de montants forfaitaires et étaient, dans certains cas, soumis à diverses conditions d’ouverture des droits. Les travailleurs atypiques étaient en général inclus dans les programmes de maintien dans l’emploi, mais des lacunes importantes subsistaient dans certains pays. L’article examine comment ces lacunes ont été comblées dans cinq États membres de l’UE. Il conclut en mettant en évidence quelques pistes pour améliorer et rendre plus adéquate la protection des revenus «extraordinaires» des travailleurs indépendants et des travailleurs atypiques en temps de crise. Sobre la base de datos originales de la Red Europea de Política Social (REPS), en el artículo se investiga hasta qué punto se incluyó a los trabajadores por cuenta propia y a los trabajadores atípicos, menos cubiertos por los sistemas de protección social “ordinarios”, en los regímenes “extraordinarios” de protección de los ingresos y de mantenimiento del empleo durante la pandemia de COVID‐19 en la Unión Europea (UE) y el Reino Unido. Con la llegada de la crisis, los países adoptaron rápidamente medidas de emergencia sin precedentes para garantizar la sustitución de los ingresos de los trabajadores por cuenta propia. No obstante, la mayoría de estos regímenes solo prestaron una ayuda básica en forma de pagos únicos que, en algunos casos, estaban sujetos a diversas condiciones de elegibilidad. En general, los trabajadores atípicos fueron incluidos en los regímenes de mantenimiento del empleo, pero en algunos países siguió habiendo deficiencias importantes. En el artículo se analiza cómo se abordaron esas deficiencias en cinco Estados miembros de la UE, y concluye destacando algunas pautas políticas para que la protección de los ingresos “extraordinaria” en tiempos de crisis sea mejor y más adecuada para los trabajadores por cuenta propia y los trabajadores atípicos. Anhand von Erhebungen des Europäischen Netzwerks für Sozialpolitik (ESPN) geht es in dem Artikel darum, inwieweit Selbstständige und Arbeitnehmer in atypischen Beschäftigungsverhältnissen, die durch „gewöhnliche“ Sozialschutzvorkehrungen weniger gut geschützt sind, während der COVID‑19‐Pandemie in der Europäischen Union und im Vereinigten Königreich bei „außergewöhnlichen“ Einkommensschutz‐ und Arbeitsplatzerhaltungsmaßnahmen berücksichtigt wurden. Nach dem Ausbruch der Krise führten die Länder schnell beispiellose Notfallmaßnahmen zum Einkommensersatz für Selbstständige ein. Dennoch boten die meisten dieser Systeme nur eine Basisunterstützung durch Pauschalbeträge und wiesen in einigen Fällen Einschränkungen aufgrund unterschiedlicher Anspruchsvoraussetzungen auf. Arbeitnehmer in atypischen Beschäftigungsverhältnissen wurden meist in die Arbeitsplatzerhaltungsmaßnahmen integriert, aber in einigen Ländern wurden erhebliche Lücken registriert. Der Artikel erörtert, wie diese Lücken in fünf EU‐Mitgliedstaaten verringert wurden. Zum Schluss wird auf einige politische Merkmale hingewiesen, mit denen sich in Krisenzeiten ein besserer und angemessenerer „außergewöhnlicher“ Einkommensschutz für Selbstständige und Arbeitnehmer in atypischen Beschäftigungsverhältnissen erreichen lässt. На примере исходных данных Европейской сети по вопросам социальной политики в статье исследуется в какой степени менее защищённые «стандартной системой социальной защиты» самозанятые и работники с нестандартной занятостью были включены в программу «чрезвычайной» поддержки доходов и программы сохранения рабочих мест в период пандемии COVID‐19 в Европейском союзе (ЕС) и Соединённом королевстве. В момент кризиса страны срочно приняли беспрецедентные экстренные меры по компенсации утраченного дохода для самозанятых. Тем не менее, большинство из этих мер обеспечили лишь базовую поддержку в виде единовременных выплат и в некоторых случаях лишь при условии соблюдения ряда требований. В целом, работники с нестандартной занятостью были включены в программы сохранения рабочих мест, но в некоторых странах оставались существенные пробелы. В статье рассматривается, как устранялись эти пробелы в пяти странах‐членах ЕС. В заключение в статье освещается ряд политических ориентиров для более эффективной и адекватной «чрезвычайной» поддержки доходов самозанятых и работников с нестандартной занятостью во времена кризиса. 基于欧洲社会政策网络(ESPN)的原始证据, 本文调查了受“常规”社会保护较少的自雇人员和非标准就业人员在欧盟和英国冠状病毒大流行期间, 被纳入“非常规”收入保护和稳岗计划的情况。发生危机时, 各国迅速为自雇人员引入了前所未有的紧急收入替代措施。然而, 这些计划中的大多数仅通过一次性支付提供基本支持, 在某些情况下, 还受限于各种资格条件。非标准就业人员一般都被纳入了稳岗计划, 但一些国家仍存在较大差距。本文讨论了五个欧盟成员国如何解决这些差距。文章最后强调了一些政策要点, 以在危机时期为自雇人员和非标准就业人员提供更好和更加充分的“非常规”收入保护。 استناداً إلى البراهين الأصلية المقدمة من الشبكة الأوروبية للسياسات الاجتماعية (ESPN)، يبحث هذا المقال في مدى إدماج العاملين لحسابهم الخاص والعاملين في القطاع غير النظامي الذين يحظون بحماية أقل في ظل 19 في الاتحاد الأوروبي والمملكة المتحدة. وقامت البلدان، عندما ضربت الأزمة، بإدراج سريع لتدابير غير مسبوقة لتعويض الدخل في حالات الطوارئ لفائدة العاملين لحسابهم الخاص. ولكن، معظم هذه الخطط وفرت دعماً بسيطاً من خلال دفع مبلغ إجمالي، وكانت في بعض الحالات، خاضعة لعدد متنوع من شروط الأهلية. وأُدمج العاملون في القطاع غير النظامي عموماً في خطط الحفاظ على مناصب العمل ولكن ظلت هنالك فجوات كبيرة قائمة في بعض البلدان. ويختم هذا المقال بإبراز بعض المؤشرات السياساتية من أجل حماية دخل "استثنائية" أفضل ومناسبة أكثر للعاملين لحسابهم الخاص والعاملين في القطاع غير النظامي في أوقات الأزمات. ‐الحماية الاجتماعية "الاعتيادية"، في خطط الحماية الاجتماعية "الاستثنائية" وخطط الحفاظ على مناصب العمل خلال جائحة كوفيد Com base em evidências originais da Rede europeia em matéria de política social (ESPN, European Social Policy Network), este artigo investiga até que ponto trabalhadores autônomos e trabalhadores não padronizados, que são menos protegidos pela proteção social "comum", foram incluídos em regimes "extraordinários" de proteção de renda e manutenção de emprego durante a pandemia de COVID‐19 na União Europeia (UE) e no Reino Unido. Quando a crise chegou, os países rapidamente introduziram medidas emergenciais sem precedentes de reposição de renda para os trabalhadores autônomos. No entanto, a maioria desses regimes proporcionou apenas apoio básico por meio de parcelas únicas e, em alguns casos, estavam sujeitos a uma variedade de condições de elegibilidade. Em geral, os trabalhadores não padronizados foram incluídos em regimes de manutenção de emprego, mas lacunas substanciais se mantiveram em alguns países. Este artigo discute como essas lacunas foram abordadas em cinco Estados‐membros da União Europeia. O artigo conclui destacando alguns indicadores políticos para uma proteção de renda "extraordinária" melhor e mais adequada para os trabalhadores autônomos e os trabalhadores não padronizados em tempos de crise.